Marketing Communication Strategy to Increase Tourism Potential in Kuningan, West Java - Mercynda Tshania (Sekolah Tinggi Pariwisata Mataram, 2022)
Located in Kuningan Regency, Putri Palutungan Waterfall is a major cultural and tourist attraction. The tourism potential of Kuningan Regency is also supported by accessibility and excellent transportation infrastructure. Several bridges were built to make it easier for tourists to access the tourist attraction area which was once divided by many rivers. With mountain forests, clear waterfalls, and fresh mountain air, Curug Putri Palutungan has a lot to offer tourists, both in terms of natural beauty and adventure. In conducting a descriptive study of the object of writing, the author uses a qualitative method, which is suitable for searching the social and communication fields in particular. In order to better understand the psychological aspects, behavior, attitudes, responses, opinions, feelings and desires of a person or group. Qualitative writing method will be used. The Youth, Sports and Tourism Office at Curug Putri Palutungan, Indonesia, uses a variety of marketing tools to promote the region's tourism potential, including banners and billboards, print media advertisements, online media advertisements, and Kuningan FM radio advertisements.